2022
DOI: 10.3389/fpsyg.2021.738211
|View full text |Cite
|
Sign up to set email alerts
|

Mind–Body Exercises for PTSD Symptoms, Depression, and Anxiety in Patients With PTSD: A Systematic Review and Meta-Analysis

Abstract: ObjectivesThis study aims to systematically analyze the effects of mind–body exercises on post-traumatic stress disorder (PTSD) symptoms, depression, and anxiety in patients with PTSD. Furthermore, it intends to provide scientific evidence-based exercise prescriptions.MethodsChinese (i.e., China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals, and Wanfang) and English (i.e., Web of Science, PubMed, the Cochrane Library, and EMBASE) databases were used as data sources to search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 104 publications
2
13
0
Order By: Relevance
“…Correspondingly, MBE was recommended as the most promising form of exercise based on the current ranking probability plot. In line with our findings, existing pairwise meta-analyses have demonstrated MBE to be an efficient adjuvant therapy in the improvement of PTSD-related symptoms, with effect sizes ranging from − 0.41 to − 0.39 [ 177 , 178 ]. Subgroup analyses in a previous meta-analysis indicated that 60–150 min of MBE 1–3 times per week over 8–16 weeks resulted in benefits to those experiencing PTSD symptoms [ 178 ].…”
Section: Discussionsupporting
confidence: 90%
“…Correspondingly, MBE was recommended as the most promising form of exercise based on the current ranking probability plot. In line with our findings, existing pairwise meta-analyses have demonstrated MBE to be an efficient adjuvant therapy in the improvement of PTSD-related symptoms, with effect sizes ranging from − 0.41 to − 0.39 [ 177 , 178 ]. Subgroup analyses in a previous meta-analysis indicated that 60–150 min of MBE 1–3 times per week over 8–16 weeks resulted in benefits to those experiencing PTSD symptoms [ 178 ].…”
Section: Discussionsupporting
confidence: 90%
“…Close to ten years later, our overview included only SRs with RCTs, and additionally assessed quality of evidence using the AMSTAR-2 tool. The current overview highlights the fact that 3 SRs without meta-analysis [30][31][32] and 7 SRs with meta-analysis [3,[23][24][25][26][27]29] reported signi cant positive effects of yoga compared to control interventions in PTSD symptoms with small to moderate size effect, while one failed to report signi cant bene t of yoga [28]. The quality of the evidence was rated as very low to moderate in 4 SRs [23][24][25]27], and 6 SRs concluded that yoga could only be considered as an adjunctive treatment to conventional approach [3, 24-26, 29, 31].…”
Section: Discussionmentioning
confidence: 99%
“…SRs were published between 2015 and 2022, including 3 to 22 RCTs dated from 1985 to 2020. Eight SRs were supplemented by a meta-analysis [3,[23][24][25][26][27][28][29].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations